2021
DOI: 10.1177/0361198121997827
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Environmental Benefits of Ridesplitting based on Observed Data from Ridesourcing Services

Abstract: The increasing emissions from the transportation sector pose substantial hazards to the environment and human health around the world. With the rapid development of information and communication technologies, ridesplitting, a form of ridesourcing service accessed via smartphone applications, enables passengers with similar origins and destinations to be matched to the same driver and share the ride. This is regarded as a promising travel mode that could mitigate air pollution. However, because of a lack of qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1477-7835.htm (Furuhata et al, 2013;Shaheen and Cohen, 2019). The practice of ridesharing in any form is interpreted as a sustainable model of transportation , which has several direct and indirect environmental benefits (Cai et al, 2019;Liu et al, 2021;Tikoudis et al, 2021).…”
Section: On-demand Ridesharingmentioning
confidence: 99%
See 1 more Smart Citation
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1477-7835.htm (Furuhata et al, 2013;Shaheen and Cohen, 2019). The practice of ridesharing in any form is interpreted as a sustainable model of transportation , which has several direct and indirect environmental benefits (Cai et al, 2019;Liu et al, 2021;Tikoudis et al, 2021).…”
Section: On-demand Ridesharingmentioning
confidence: 99%
“…The practice of ridesharing in any form is interpreted as a sustainable model of transportation (Zhang and Zhang, 2018), which has several direct and indirect environmental benefits (Cai et al. , 2019; Liu et al. , 2021; Tikoudis et al.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also study three built environment factors (density, economic prosperity, and land-use mix) and find they are correlated with shared-ride trips. Finally, Liu et al used a localized MOVES (EPA's MOtor Vehicle Emission Simulator) model combined with the GPS trajectories of Didi trips in Chengdu, China and showed that ridesplitting can decrease travel distance by 22% compared with private trips, with average reductions of 10.601 g of CO, 0.691 g OF NO x , and 1.424 g of HC per ridesplitting trip (6).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research (4)(5)(6) on ridesplitting services has shown their impact on decreasing vehicle miles traveled on the road network, thereby relieving congestion and harmful emissions. When congestion levels increase in cities, it is important to analyze and model people's choices of different services provided by TNCs.…”
mentioning
confidence: 99%
“…UberPool is said to save 120 tons of carbon dioxide emissions in San Francisco where it accounts for approximately 50% of Uber rides in the city, and to save 7.9 million driving miles in Los Angeles ( 5 ). Evidence on the potential of this shared ridesourcing model was provided by Santi et al ( 6 ) in a simulation-based study using New York City (NYC) taxi trips, and on the environmental benefits by comparing the shared versus not-shared scenarios’ respective emissions using DiDi Chuxing trips in Chengdu, China ( 7 ). Therefore, understanding the behavior of willingness-to-share (WTS) ridesourcing trips is not only pertinent to comprehending the system from the demand side, but also to boosting and operationalizing those benefits as well.…”
mentioning
confidence: 99%